Does meaningful work mediate the relationship between empowering leadership and mental health? Evidence from Malaysian SME employees - Jalil, Muhammad Farhan; Tariq, Bilal; Ali, Azlan (Frontiers in Sociology, 2023)
Introduction In Malaysia, small and medium enterprises (SMEs) account for more than half of all employment and 98.7% of all businesses. There is little research on empowering behaviors in SMEs, despite leadership empowerment being often practiced. Therefore, the study aims to investigate how empowering leadership affects employees' mental health. The study also reveals meaningful work's role in mediating the relationship between empowering leadership and employees' mental health. Methods A stratified random sample approach was used to collect data from 516 employees of Malaysian SMEs. The data was analyzed, and the hypothesis was tested using structural equation modeling (AMOS 21.0) with bootstrap confidence intervals computed to evaluate the mediating effect. Results The results demonstrate that empowering leadership significantly improves employees' mental health. Furthermore, the association between empowering leadership and mental health is partially mediated by meaningful work. Discussion This study contributes to the present empowering leadership-meaningful work-mental health model for SME employees, which reduces stress and anxiety at the workplace and positively impacts psychological empowerment and their capacity to control their overall emotions in instances of success.